RUANG KERJA BERSAMA DI BANJARBARU - Annisa Intan Puteri; Mohammad Ibnu Saud (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The Gig Economy is one result of the influence of the development of internet technology, defined as the trend of working with a short-term contract system, not fixed, but has the advantage of flexibility. Coworking Space is here to offer space rentals that can accommodate high-mobility work activities, targeting consumers; Generation Z as a group of actors who dominate the Gig Economy trend. Greater Flexibility, or better flexibility, is a problem that will be resolved in the design of the Coworking Space in Banjarbaru. Workspaces that have high flexibility are considered the right strategy to meet the needs of high mobility as well. The concept of Fluidity Space is applied using the superimposition method; separate the elements of the event forming the architecture, then rearrange them randomly to form three relationship programs, namely; reciprocity, indifference and conflict. These three relationships will be used to test the flexibility of spaces so that high fluidity is achieved to answer the flexibility problem in the Coworking Space in Banjarbaru.